Optimisation du milieu de culture pour la production des bactériocines des bactéries lactiques - Makhlouf, Sarah; Souane, Asmae (My University, 2017)
Lactic bacteria are naturally part of our environment. It has long been recognized that lactic acid bacteria have the property of producing antimicrobial substances. Indeed, lactic acid bacteria have the particularity to synthesize inhibiting substances, among others bacteriocins. The aim of our work is to optimize the production of bacteriocins of 4 lactic strains by studying different parameters that may be responsible for the increase in bacteriocin production. The study of macroscopic, microscopic, biochemical and physiological characteristics (fermentation type, arginine hydrolysis (ADH), sugar fermentation, growth on Sherman blue milk, heat resistance, NaCl effect: 4% and 6.5%, pH = 9.6 and growth at different temperatures) were used to orient identification to: Enterococcus sp Subsequently, we performed an optimization on the MRS medium based on the modification of various sources composing the culture medium: source of nitrogen, carbon and potassium by studying in parallel the incubation time, Development of growth kinetics, as well as the effect of temperature and pH. The antimicrobial activity of the lactic bacteria was demonstrated after each optimization by the AWDA method using pathogenic bacteria, namely Escherichia coli, Proteus mirabilis and Staphylococcus aureus. The results obtained show that some sources composing the culture medium act only on the growth of the bacterial strain while others act on the production of bacteriocin. The optimized MRSm medium gave much better result compared to the control which is the MRS. We find large zones of inhibition between 26 to 30 mm for S. aureus, while diameters are 22 to 26 mm for E.coli and diameters between 27 to 32 mm for P.mirabilis.
Keywords: Lactic bacteria; bacteriocin; Optimization of the culture medium; pathogenic bacterium; antimicrobial power; البکتيريا اللبنية; البکتيريوسين; تحسين وسط الاستزراع; البکتيريا المسببة للأمراض; قوة مضادات الميکروبات; Bactéries lactiques; bactériocine; Optimisation du milieu de culture; bactérie pathogène; pouvoir antimicrobien